Pengaruh Komitmen Kerja, Kompetensi Kerja Dan Kepemimpinan Transformasional Terhadap Kinerja Kepala Sekolah Dasar Di Kecamatan Gumelar Kabupaten Banyumas - Diyati Diyati (Public Policy and Management Inquiry, 2020)
The role of the Principal as the highest leader in the School is very important. Principal performance can be influenced by several aspects including work commitment, work competence and transformational leadership. The purpose of this study was to analyze how much influence Work Commitment, Work Competence and Transformational Leadership had on the Performance of Primary School Principals in Gumelar District, both partially and together. The method used is quantitative. The sampling technique used census techniques. Data analysis uses frequency distribution, Kendall tau c correlation, Kendall concordance w and ordinal regression. The results showed that there was no positive and significant influence between Work Commitment (X1) on Performance (Y) of Primary School Principal in Gumelar District, there was a positive and significant effect between Work Competence (X2) on Performance (Y) of Primary School Principal in Gumelar Sub-district by 40.2 percent and the rest influenced by other variables, there is a positive and significant effect between Transformational Leadership (X3) on Performance (Y) Primary School Principal in Gumelar District by 60.2 percent and the rest is influenced by other variables. other variables, there is a positive and significant effect together between Work Commitment (X1), Work Competence (X2), and Transformational Leadership (X3) on the Performance (Y) of Primary School Principal in Gumelar District by 94.1 percent and the rest influenced by other variables.